SVKEGIONAL GEOLOGICAL POSITION OT CARBONATE-PHTANITE I SEDIMENTS OF BOGAMBIR SUITE - Porshnyakov G.S.; Fidaev D.; Yu B. (My University, 1998)
Carbonate-phtanite sediments of Bogambir suite (Uppermost Precambrian, Northern Nuratau Mountains, Uzbekistan) are to be discriminated from Ordovician and Silurian in the imbricated Variscian structure of Bogambir range. The phtanites show partly late metasomatic origin. Bogambir suite together with synchronous and similar black cherts and carbonates of Kyzylkum, Tamerlan Gates etc. presents the early rift phtanite formation in Tien-Shan. Posterior phtanite sedimentation in Cambrian-Early Silurian emerged locally.
Keywords: Ordovician; Precambrian; Silurian; Cambrian; Paleozoic::Ordovician; Precambrian; Paleozoic::Silurian; Paleozoic::Cambrian; Палеозой::Силурийская; Палеозой::Ордовикская; Палеозой::Кембрийская; Докембрий